2022
DOI: 10.1093/jmcb/mjac001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aryl hydrocarbon receptor signaling promotes the terminal differentiation of human erythroblasts

Abstract: The aryl hydrocarbon receptor (AHR) plays an important role during mammalian embryo development. Inhibition of AHR signaling promotes the development of hematopoietic stem/progenitor cells. AHR also regulates the functional maturation of blood cells, such as T cells and megakaryocytes. However, little is known about the role of AHR modulation during the development of erythroid cells. In this study, we used the AHR antagonist StemRegenin 1 (SR1) and the AHR agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The percentage of AHR sense expressing cells also decreased dramatically, from approximately 40% in progenitors, to ~10% in immature NK cells, and less than 2% in mature NK cells. This indicates that AHR is downregulated during differentiation, in line with observations that AHR antagonism increases NK cell differentiation (Lordo et al, 2021; Chen et al, 2022).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The percentage of AHR sense expressing cells also decreased dramatically, from approximately 40% in progenitors, to ~10% in immature NK cells, and less than 2% in mature NK cells. This indicates that AHR is downregulated during differentiation, in line with observations that AHR antagonism increases NK cell differentiation (Lordo et al, 2021; Chen et al, 2022).…”
Section: Resultssupporting
confidence: 88%
“…The presence of an opposing promoter in the first intron of the AHR gene (asPro1), potentially creating an on/off-switch, is intriguing, especially with regard to a recent study that demonstrated the ability of AHR antagonists to enhance ESC differentiation (Chen et al, 2022). If the function of the asPro1 promoter is to downregulate AHR expression in differentiating cells, then its expression should be limited to early progenitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, alternative protocols that show highly efficient production of hemoglobin β using different approaches, such as immortalization of erythroid precursor cells and modulation of BCL11A expression [ 25 , 26 , 63 ], in vivo maturation in NOD/SCID mice [ 64 ], or using cells treated with human platelet lysate [ 63 ], should be further assessed. Recently, Chen et al reported that erythroid terminal differentiation was improved in a culture of HSPCs derived from human embryonic stem cells by adding an aryl hydrocarbon receptor antagonist [ 65 ], and this represents a less laborious approach that is compatible with SCD disease models.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood counts were measured by SYSMEX XT-1800i. Blood smear was stained by May-Grunwald Giemsa (MGG) as described previously [ 20 ].…”
Section: Methodsmentioning
confidence: 99%